2000
DOI: 10.1093/gerona/55.5.b220
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Oxidatively Modified Protein Is Associated With a Decrease of Proteasome Activity and Content in Aging Epidermal Cells

Abstract: For the process of aging in epidermal cells to be characterized, the status of oxidized and damaged protein accumulation and removal by the proteasome has been investigated. Modified protein content and proteasome activity were assayed in lysates of epidermal cells from donors of different ages. Increased levels of oxidized proteins, glycated proteins, and proteins modified by the lipid peroxidation product 4-hydroxy-2-nonenal were observed in cells from old donors. At the same time, a decline of chymotrypsin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
114
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(121 citation statements)
references
References 45 publications
6
114
0
1
Order By: Relevance
“…A number of studies have demonstrated that impairment of proteasome function is associated with cellular senescence; however, the available data are fragmented and contradictory (15)(16)(17)(18)(19)(20)(21)42). To understand the involvement of the proteasome, we have taken a detailed molecular and biochemical approach of WI38 fibroblasts undergoing replicative senescence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have demonstrated that impairment of proteasome function is associated with cellular senescence; however, the available data are fragmented and contradictory (15)(16)(17)(18)(19)(20)(21)42). To understand the involvement of the proteasome, we have taken a detailed molecular and biochemical approach of WI38 fibroblasts undergoing replicative senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Using oligonucleotide array techniques, the expression of several proteasome subunits has been found to decline with age in: human dermal fibroblasts (24), the skeletal muscle of the C57BL/6 mouse (25), and the epididymis of the Brown Norway rat (26). Similarly, decreased proteasome quantity has been observed in senescence MRC5 human embryonic fibroblasts (17) as well as in skin fibroblasts and keratinocytes derived from aged donors (14,16,18); in contrast, unchangeable proteasome content has been reported in few other studies (19 -21). However, in all these preliminary studies only one or two representative subunits of the 20 S complex were analyzed.…”
mentioning
confidence: 99%
“…As mentioned, FOXOs are involved in the proteasome system degradation of short‐lived and regulatory cytosolic proteins. Aging is associated with a decreased proteasomal activity, leading to excess of damaged proteins in muscle, liver, and heart (Conconi et al ., 1996; Petropoulos et al ., 2000; Bulteau et al ., 2002; Husom et al ., 2004). Moreover, pathogenesis of neurodegenerative disorders such as Parkinson's, Alzheimer's, or Huntington's disease is generally related to an abnormal ubiquitin‐proteasome mechanism as either a primary cause or secondary consequence (Ciechanover & Brundin, 2003; Kikis et al ., 2010; Webb & Brunet, 2014).…”
Section: Foxo and Autophagymentioning
confidence: 99%
“…Aging is associated with a decreased proteasomal activity, leading to excess of damaged proteins in muscle, liver, and heart (Conconi et al ., 1996; Petropoulos et al ., 2000; Bulteau et al ., 2002; Husom et al ., 2004). Foxo3 has been shown to be a transcriptional regulator of muscle‐specific E3 ubiquitin ligases, which are major effectors of protein degradation in muscle (Sandri et al ., 2004, 2006; Stitt et al ., 2004).…”
Section: Animal Modelsmentioning
confidence: 99%
“…It was shown that the proportion of damaged proteins increases with replicative senescence in several cell types, including human diploid fibroblasts (HDF) (Ahmed et al 2007;Grune et al 2001;Petropoulos et al 2000) and human umbilical vein endothelial cells (HUVEC) (Unterluggauer et al 2007). However, the cellular proteins that are targeted by oxidative modifications have not been identified in most cases.…”
Section: Introductionmentioning
confidence: 99%